ISO/IEC MPEG-4 High-Definition Scalable Advanced Audio Coding - Geiger, Ralf; Yu, R; Herre, Jürgen; Rahardja, Susanto; Kim, Sang-wook; Lin, Xiao; Schmidt, Markus (120th AES Convention, 2006)
Recently, the MPEG Audio standardization group has successfully concluded the standardization process on technology for lossless coding of audio signals. This paper provides a summary of the Scalable Lossless Coding (SLS) technology as one of the results of this standardization work. MPEG-4 Scalable Lossless Coding provides a fine-grain scalable lossless extension of the well-known MPEG-4 AAC perceptual audio coder up to fully lossless reconstruction at word lengths and sampling rates typically used for high-resolution audio. The underlying innovative technology is described in detail and its performance is characterized for lossless and near-lossless representation, both in conjunction with an AAC coder and as a stand-alone compression engine. A number of application scenarios for the new technology are discussed finally.
herre_papers_perceptual_audio_coding